The impact of resveratrol-enriched bread on cardiac remodeling in a preclinical model of diabetes - Silva, AFR (2023)
The World Health Organization aims to stop the rise of diabetes by 2025, and diet is one of the most efficient non-pharmacological strategies used to prevent it. Resveratrol (RSV) is a natural compound with anti-diabetic properties, and incorporating it into bread is a suitable way to make it more accessible to consumers as it can be included as part of their daily diet. This study aimed to evaluate the effect of RSV-enriched bread in preventing early type 2 diabetes cardiomyopathy in vivo. Male Sprague Dawley rats (3 weeks old) were divided into four groups: controls with plain bread (CB) and RSV bread (CBR), and diabetics with plain bread (DB) and RSV bread (DBR). Type 2 diabetes was induced by adding fructose to the drinking water for two weeks followed by an injection of streptozotocin (STZ) (40 mg/kg). Then, plain bread and RSV bread (10 mg RSV/kg body weight) were included in the rats’ diet for four weeks. Cardiac function, anthropometric, and systemic biochemical parameters were monitored, as well as the histology of the heart and molecular markers of regeneration, metabolism, and oxidative stress. Data showed that an RSV bread diet decreased the polydipsia and body weight loss observed in the early stages of the disease. At the cardiac level, an RSV bread diet diminished fibrosis but did not counteract the dysfunction and metabolic changes seen in fructose-fed STZ-injected rats.